The effect of a kind of whey protein (Ma'oljobon) on Insomnia: A randomized clinical trial. (February 2019) - Navabzadeh, Maryam; Hashem-Dabaghian, Fataneh; Shojaii, Asie; Kazemi, Toba; Hadinia, Javad; Ghods, Taraneh; Ghods, Roshanak
Highlights: Insomnia is defined as a difficulty in the start of sleeping or lack of refreshing sleep. In Persian medicine, the cause of insomnia is the brain hot and dry dys-temperament. Ma'aljobon is a kind of whey protein with wet and cold temperament. Ma'aljobon is recommended as a moistening food for dry tempered patient. Ma'aljobon was able to reduce the severity of insomnia, significantly.